2021
DOI: 10.3390/foods10071526
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Seaweed Supplementation in Cows on Milk Macrominerals, Trace Elements and Heavy Metal Concentrations

Abstract: This study investigated the effect of seaweed supplementation in dairy cow diets on milk yield, basic composition, and mineral concentrations. Thirty-seven Icelandic cows were split into three diet treatments: control (CON, no seaweed), low seaweed (LSW, 0.75% concentrate dry matter (DM), 13–40 g/cow/day), and high seaweed (HSW, 1.5% concentrate DM, 26–158 g/cow/day). Cows were fed the same basal diet of grass silage and concentrate for a week, and then were introduced to the assigned experimental diets for 6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 69 publications
1
13
0
Order By: Relevance
“…Therefore, the dietary supplementation with SOP at 70 g/cow per day (about 0.35% DMI/day) could not remarkably improve milk productivity and quality under Vietnam dairy husbandry conditions. In agreement with our study, Newton et al (2021) showed that the diet with a small amount of seaweed supplementation (0-158 g/cow per day) for dairy cows was not adequate to improve considerably these parameters. It was also demonstrated that the dietary seaweed supplementation for dairy cows did not affect milk productivity and basic compositions (Lopez et al, 2016;Antaya et al, 2019;Hein, 2021).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Therefore, the dietary supplementation with SOP at 70 g/cow per day (about 0.35% DMI/day) could not remarkably improve milk productivity and quality under Vietnam dairy husbandry conditions. In agreement with our study, Newton et al (2021) showed that the diet with a small amount of seaweed supplementation (0-158 g/cow per day) for dairy cows was not adequate to improve considerably these parameters. It was also demonstrated that the dietary seaweed supplementation for dairy cows did not affect milk productivity and basic compositions (Lopez et al, 2016;Antaya et al, 2019;Hein, 2021).…”
Section: Discussionsupporting
confidence: 92%
“…In addition, Baek et al (2004) and Lee et al (2005) indicated that seaweed added 4% DMI/day (800 g/cow per day) into diets of dairy cows significantly increased milk yield, but not milk compositions. Interestingly, Newton et al (2021) revealed that the low supplementation of seaweed (13-40 g/cow per day) did not increase milk yield and quality whereas the dietary high seaweed concentration (26-158 g/cow per day) improved considerably some milk quality parameters (milk protein and casein) without a difference in milk yield and other milk compositions (milk fat, lactose, free fatty acids, SCC). Therefore, there was a wide variation in the effectiveness of SOP supplementation on milk performance and quality in the various supplemented concentrations in recent studies (Baek et al, 2004;Lee et al, 2005;Newton et al, 2021) and only a noticeable enhancement with seaweed supplementation from 90 g/cow per day (equivalent to 0.4% DMI/day) (Cruywagen et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In the current experiment, the iodine concentration was 35 mg/kg DM for treatment AN2.5 and 2.75 mg/kg DM for treatment FV2.5. Additionally, it was shown that the iodine concentration in milk follows a dose-response relationship with iodine intake ( Antaya et al, 2015 ; Newton et al, 2021 ). Humans, especially children, are even more sensitive to iodine poisoning than ruminants ( Zimmermann et al, 2005 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, no data exist regarding the effect of key aspects of organic feed (such as white clover) on milk-iodine concentration, or whether the seasonal effects seen in the past are as pronounced today with the increasing practice for year-round housing for dairy cows on large farms. Furthermore, seaweed is starting to be used in farming (e.g., to reduce greenhouse gas emissions), either given to cows or used as a fertilizer on grassland; seaweed use in the dairy industry has been shown to increase milk-iodine concentration ( 78 , 79 ) but further research on ways to incorporate it without risking iodine excess is required.…”
Section: Dairy Nutrition Across the Life Course–future Research And I...mentioning
confidence: 99%